A planar‐printed E‐shaped omnidirectional magneto‐electric dipole antenna for WWAN/LTE applications. Issue 8 (August 2014) - Feng, Botao; Yin, Sixing; Li, Shufang
ABSTRACT A planar‐printed E‐shaped dual‐wideband magneto‐electric (ME) dipole antenna for WWAN/LTE applications is proposed. Through changing the surface‐current distributions, an E‐shaped electric‐dipole structure is used to provide a dual‐wideband. Besides, to reduce the size of the antenna and improve impedance matching, a novel feeding structure designed with inverted U‐shaped tapered line and meandering L‐shaped line is introduced. Finally, without conventional vertical ground planes, a small‐size one is printed on the back side of the substrate to attain stable gains and omnidirectional radiation patterns. The antenna prototype can attain a bandwidth of 31.6% (0.80–1.10 GHz) with a stable gain of 3.1 ± 0.5 dBi for the lower band, and a bandwidth of 47.5% (1.67–2.71 GHz) with a gain of 3.9 ± 0.7 dBi for the upper band, covering the frequency bands for WWAN/LTE systems. In comparison with the existing ME dipole antennas, the proposed antenna can be easily fabricated at low cost which makes it suitable for WWAN/LTE applications. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1734–1739, 2014